2021
DOI: 10.1038/s41598-021-91912-x
|View full text |Cite
|
Sign up to set email alerts
|

Potential risk of disease modifying therapies on neoplasm development and coadjutant factors in multiple sclerosis outpatients

Abstract: Neoplasm development in Multiple Sclerosis (MS) patients treated with disease-modifying therapies (DMTs) has been widely discussed. The aim of this work is to determine neoplasm frequency, relationship with the prescription pattern of DMTs, and influence of the patients’ baseline characteristics. Data from 250 MS outpatients were collected during the period 1981–2019 from the medical records of the Neurology Service of the HUPM (Hospital Universitario Puerta del Mar)—in Southern Spain—and analysed using Cox mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The duration of exposure to dimethyl fumarate was found to be protective, with a hazard ratio of 0.725 (95% confidence interval (CI) = 0.507–1.036, p = 0.077), indicating a reduction in cancer risk of 27% for each year of treatment. 55 In contrast, a study using data from the worldwide Vigibase between 1 January 2000 and 9 January 2019 demonstrated a significant association between dimethyl fumarate and the reporting of cancer in the univariate analysis. The association was more pronounced in females (76.9%) and predominantly observed in individuals aged between 45 and 64 years (58.4%), with a median time to onset of 13 months.…”
Section: Resultsmentioning
confidence: 92%
“…The duration of exposure to dimethyl fumarate was found to be protective, with a hazard ratio of 0.725 (95% confidence interval (CI) = 0.507–1.036, p = 0.077), indicating a reduction in cancer risk of 27% for each year of treatment. 55 In contrast, a study using data from the worldwide Vigibase between 1 January 2000 and 9 January 2019 demonstrated a significant association between dimethyl fumarate and the reporting of cancer in the univariate analysis. The association was more pronounced in females (76.9%) and predominantly observed in individuals aged between 45 and 64 years (58.4%), with a median time to onset of 13 months.…”
Section: Resultsmentioning
confidence: 92%
“… 117 Overall, the malignancy rate in patients treated with DMF is similar to age- and sex-matched individuals without MS. 118 Duration of DMF treatment was concluded as a risk protective factor against neoplasms, in a small Spanish study. 119 Recent database analyses have produced conflicting results, with one finding no evidence of an increased cancer risk 120 and the other being the first publication to find an increased risk of neoplasm with DMF. 121 Consequently, it may be prudent to be vigilant in checking for cancer in DMF-treated patients, but this does not yet support a malignancy rate higher than the general population.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies regarding the effect of DMTs on cancer have obtained contradictory results, with some resulting in an increased risk of cancer, while others have shown no increased cancer risk. This disparity is further complicated by the various types of DMTs used in patients with MS [ 20 , 28 31 ]. A Danish nationwide cohort study also found that DMTs in Danish MS patients were neither accompanied by an increase in cancer incidence nor an increase in cancer-specific mortality [ 18 ].…”
Section: Discussionmentioning
confidence: 99%